THE INFLUENCE OF CHASE METHOD AND TEAM BASE PROJECT-BASED LEARNING MODELS ON LEARNING OUTCOMES IN BASIC PHYSICS AND CHEMISTRY CONCEPTS COURSES PGSD FIP UNIMED STUDENTS - Suyit Ratno; Andri Kristianto Sitanggang (Universitas Negeri Medan, 2022)
This research aims to determine whether there is an influence of the Chase method and Team Base Project-based learning model on learning outcomes in the basic physics and chemistry concepts course of PGSD FIP UNIMED students. The research method used is a quantitative research method with a type of correlation research. The research population is all PGSD FIP UNIMED students in the second semester of the 2021/2022 academic year. The sample taken was 42 students using purposive sampling data collection techniques. The data in this study were obtained through a learning outcomes test. The test results used have been tested for validity and reliability. Meanwhile, the data analysis technique used is correlation. From the calculation results obtained t count is 56.414, then the result is compared with t table at a significance level of 5% which is 2.018. This shows that t count > t table which means that there is an influence of the Chase method and Team Base Project-based learning model on learning outcomes in the basic physics and chemistry concepts course of PGSD FIP UNIMED students. Meanwhile, the use of the Chase method and Team Base Project-based learning model contributed 98.8% to learning outcomes in the basic concepts of physics and chemistry courses of PGSD FIP UNIMED students, while the remaining 1.2% was influenced by other factors.